Rapid reappearance of Plasmodium falciparum after drug treatment among Senegalese adults exposed to moderate seasonal transmission - Sokhna, Cheikh-Sadibou; Faye, Farba B.K.; Andre´ Spiegel, Andre´; Dieng, Hamady; Trape, Jean-Francois (The American Society of Tropical Medicine and Hygiene, 2001)
To investigate the relationship between the entomologic inoculation rate (EIR) and time to reappearance of malaria parasites after radical treatment under moderate seasonal transmission conditions, a study was undertaken in a mesoendemic area of Senegal where malaria transmission is concentrated over an annual three-month period and averages 12 infective bites per person per year. A three-day course of quinine was administered to 48 asymptomatic adults between 19 and 66 years of age. Malaria transmission and parasitemia were monitored every week for two months and cases of fever or symptoms were investigated as part of a daily clinical surveillance. The proportion of persons reinfected at Days 28, 35, and 56 was 25%, 38%, and 54%, respectively. Adults less than 40 years of age had a shorter time to reinfection. In this age group, the median Plasmodium falciparum reappearance time was 28 days, and it was estimated that only one infected mosquito bite was able to induce a patent infection among half of the subjects. Only 8% (2 of 26) of the reinfections caused a clinical attack. These data are discussed in the light of previous studies conducted among adults naturally exposed to intense perennial transmission or among naive volunteers receiving artificial challenges. Rapid reinfection occurs at very low EIRs and dramatic differences in actual and cumulated exposure to infected mosquito bites poorly affect the median time to reappearance of malaria parasites in endemic populations.